Gender differences, attachment styles, self-esteem and romantic relationships in Thailand - Wongpakaran T. (2014)
In this study we explore the association between attachment dimension (anxiety and avoidance), attachment style (secure, preoccupied, fearful and dismissing), self-esteem and romantic relationships, as determined by relationship status, relationship satisfaction and the length of relationships in 398 young Thai people. For the results, males scored higher in terms of both attachment anxiety and avoidance than the females, and this is consistent with other Asian cultures when compared to their western counterparts. It was found that non-romantic attachment as well as self-esteem does not predict the status of a relationship; however, romantic attachment avoidance predicts the level of relationship satisfaction, though with no difference between men and women. The lack of variables associated with the length of a relationship and relationship satisfaction, highlight the fact that other involved factors remain unstudied. The limitations of the study are also discussed. © 2011 Elsevier Ltd.